The retropharyngeal reduction plate for atlantoaxial dislocation: a finite element analysis - Kong, Weiqing; Du, Yukun; Li, Jianyi; Shao, Jiale; Xi, Yongming (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To investigate the biomechanical property of retropharyngeal reduction plate comparing the traditional posterior pedicle screw-rod fixation by using finite element analysis.Two three-dimensional finite element digital model of retropharyngeal reduction plates and posterior pedicle screw-rod fixation were constructed and validated based on the Dicom data from C1-C4. The biomechanical finite element analysis of two internal fixations were respectively measured and calculated under different conditions including flexion, extension, bending and rotation. Results Besides of the backward extension, there were no significantly difference of the maximum von Mises stress between retropharyngeal reduction plate and posterior pedicle screw fixation under other movement conditions. The retropharyngeal reduction plate has more uniform distribution under different conditions, such as flexion, extension, bending and rotation. respectively. The stress tolerance of two internal fixations was basically consistent in flexion, extension, left and right bending, respectively.The retropharyngeal reduction plate has relatively good biomechanical stability without obvious stress concentration under different movement conditions.There is the application prospect of being one of the fixation choices for the treatment of atlantoaxial dislocation.